Effect of Islamic-based repentance therapy on the prevention of Post-traumatic Stress Disorder (PTSD) - Uyun, Qurotul; Jaufalaily, Nahdhata; Witruk, Evelin; Kurniawan, Irwan Nuryana (Faculty of Psychology and Health - Universitas Islam Negeri Walisongo Semarang, 2020)
This research is based on the tragedy of a road traffic accident that led to a student's death. Her classmates felt lost and experienced symptoms of Post-traumatic Stress Disorder (PTSD). The purpose of the study is to examine the effectiveness of repentance and istighfar therapy to prevent PTSD. The research was based on a quasi-experimental design that consisted of six sessions in three meetings and homework for four weeks. The study participants were 14 students who experienced PTSD symptoms. They completed a scale before the intervention (pre-test), after completion of the intervention (post-test), and three weeks after the post-test. The paired sample test analysis results show that there were significant differences in the trauma scores pre-therapy and post-therapy. The effect size estimation results show that the effect of repentance and istighfar therapy was in the large effect size category; that is, 80.9% of the trauma variations could be explained (caused) by repentance therapy and istighfar. The research implies that such therapy can be predicted to be effective in reducing psychological disorders, as long as they are willing to be seriously involved in each stage of the therapy process that has been determined.